Integration of stress and leptin signaling by CART producing neurons in the rodent midbrain centrally projecting Edinger-Westphal nucleus - Xu, Lu; Kozicz, Tamas; Janssen, Donny; Roubos, Eric W.; Leshan, Rebecca L.; Myers, Martin G.; Gaszner, Balazs; van der Knaap, Noortje (Frontiers in Neuroanatomy, 2014)
Leptin targets the brain to regulate feeding, neuroendocrine function and metabolism. The leptin receptor is present in hypothalamic centers controlling energy metabolism as well as in the centrally projecting Edinger–Westphal nucleus (EWcp), a region implicated in the stress response and in various aspects of stress-related behaviors. We hypothesized that the stress response by cocaine- and amphetamine-regulated transcript (CART)-producing EWcp-neurons would depend on the animal’s energy state. To test this hypothesis, we investigated the effects of changes in energy state (mimicked by low, normal and high leptin levels, which were achieved by 24 h fasting, normal chow and leptin injection, respectively) on the response of CART neurons in the EWcp of rats subjected or not to acute restraint stress. Our data show that leptin treatment alone significantly increases CART mRNA expression in the rat EWcp and that in leptin receptor deficient (db/db) mice, the number of CART producing neurons in this nucleus is reduced. This suggests that leptin has a stimulatory effect on the production of CART in the EWcp under non-stressed condition. Under stressed condition, however, leptin blunts stress-induced activation of EWcp neurons and decreases their CART mRNA expression. Interestingly, fasting, does not influence the stress-induced activation of EWcp-neurons, and specifically EWcp-CART neurons are not activated. These results suggest that the stress response by the EWcp depends to some degree on the animal’s energy state, a mechanism that may contribute to a better understanding of the complex interplay between obesity and stress.